Uso de plantas medicinais como alternativa para o tratamento das cefaleias - Silva, Amanda Araújo da; Valença, Marcelo Moraes (Headache Medicine, 2014)
The World Health Organization (WHO) considers headache the most common disease of the nervous system that can generate various disabilities. However, there is an underestimation and underreported hindering the impact of public health. The International Classification of Headache Disorders (ICHD) considers the tension-type headache and migraine as the most common types of primary headache. The treatment of headache has pervaded the medical model (biomedical) extending to the traditional, acknowledged by the use of medicinal plants. From 1980, the term "complementary medicine" was inserted in order to reconcile the two models. According to the National Health Surveillance Agency (Anvisa), medicinal plants are plant species that are natural or cultured with the therapeutic purpose; ease of use as well as to keep the tradition, is the most viable for many communities to treat and prevent diseases, besides maintaining health. The use of plants is beyond cure and includes spiritual power and magic. The use of the plant varies with the health problem, but in all cases, there is a false belief that natural medicines have no contraindication, which offers serious risks to the consumers. Beliefs are ideas that consolidate over time, in that people consider more valid than logic, which may have tendentious and emotional nature. The purpose of this study was to visit popular markets in the Greater Recife region in the search for information on the use of medicinal plants for the treatment of headache.